Conservative management of airway tear as a complication of silicone endobronchial stenting in bronchomalacia secondary to endobronchial tuberculosis - Huan, Nai‐Chien; Khai, Lip Ng; Nasaruddin, Mona Zaria; Muhammad, Noorul Afidza; Daut, Ummi Nadira; Abdul Rahaman, Jamalul Azizi (John Wiley & Sons, 2020)
Tracheobronchial stenosis due to tuberculosis (TSTB) is a potentially debilitating complication of endobronchial tuberculosis (EBTB). Endobronchial interventions including silicone stent insertion is an acceptable approach to improve quality of life among patients with TSTB. However, little is known about the optimal management strategy for patients with bronchomalacia secondary to EBTB (B‐EBTB) and whether stent‐related complication rates are higher among this group of patients. Herein, we report two patients with B‐EBTB who unfortunately developed bronchial tear related to silicone endobronchial stenting. Both patients were successfully managed conservatively without the need for emergency open surgery. We hypothesize that endobronchial intervention might be more beneficial for patients with pure TSTB and might be riskier in cases of bronchomalacia with reduced airway thickness and loss of airway cartilaginous support. More future studies are needed to bridge the current gap in knowledge regarding the optimal management and role of endobronchial interventions among patients with B‐EBTB.